Environmental Education in Indonesia: Mapping the Needs of Teachers and Students within the Framework of National Education Transformation - Utari Akhir Gusti; Asep Ihsanudin; Ade Munawar Luthfi; Haryo Mojopahit; Muhammad Shirli Gumilang (Bioeducation Journal, 2026)
National education transformation requires contextual, sustainable learning innovations rooted in the socio-cultural realities of students. This study aims to analyze the role of local community involvement and the utilization of local knowledge as learning resources in supporting the three pillars of education, as well as to identify student learning needs and teacher pedagogical competencies in the implementation of the CLEAR-based ADAB Project. This study uses a mixed methods approach with a convergent parallel design. The sample consisted of 123 respondents, comprising 21 teachers and 102 students from various educational levels and regions in Indonesia. Data were collected through closed and open questionnaires, then analyzed descriptively, quantitatively, and qualitatively. The results showed that local community involvement and the integration of local knowledge significantly increased the relevance and meaningfulness of learning. Students need contextual, enjoyable, and relevant learning that is connected to real life. Meanwhile, teachers need to strengthen their pedagogical competencies in designing active, differentiated, and project-based learning. In addition, environmental education project learning integrated with issues of conservation, food security, and climate change has proven to be an effective strategy in building environmental literacy, character, and social awareness. These findings confirm that the synergy between local knowledge, community involvement, and teachers' pedagogical competence is an important foundation for realizing holistic, contextual, and sustainable education in Indonesia.